(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the feat of the Uzbeks at the front and in the rear during the Second World War from a socio-philosophical point of view. The concepts of courage, patriotism, human duty and spiritual self-sacrifice are philosophically clarified, and the spiritual significance of these processes for the modern generation is revealed.